“UNA GUERRA DE ACENTOS Y PALABRAS” . EL DERECHO AL IDIOMA EN LOS MEDIOS DE COMUNICACIÓN DE PUEBLOS INDÍGENAS - Doyle, Maria Magdalena (Revista Debates Insubmissos, 2023)
The article analyzes the centrality that the right to language acquires in the case of the media of indigenous peoples. A conceptual analysis of the link between both rights is proposed and the way in which the exercise of the right to language is a central foundation of indigenous struggles to have their own means of communication is analyzed. In turn, it is proposed to recognize the characteristics of this fight for the right to language in the context of indigenous disputes around communication rights in Argentina, as well as in the experience of an indigenous radio station in Argentina in particular.